Exploration of Fungal and Lichen Diversity in The Waitatiri Watershed, Central Maluku: Ecological Potential - Bahri, Husnaini; Tuapattinaya, Prelly M.J; Karuwal, Ritha Lusian (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
The Waitatiri Watershed (DAS) in Central Maluku is one of the tropical ecosystems that supports biodiversity, including fungi and lichens. Fungi play a significant role in organic matter decomposition, while lichens serve as bioindicators of air and environmental quality. However, information regarding the diversity of these organisms in the Waitatiri watershed remains limited. This study employed purposive random sampling to explore fungi and lichens in the Waitatiri watershed. Samples were collected from substrates such as living tree trunks, deadwood, bark, rocks, and soil. Initial identification was conducted using digital applications, followed by detailed identification based on relevant scientific literature. Data were analyzed descriptively to describe species types, distribution, and ecological roles. The study identified 10 fungal species from the phylum Basidiomycota and 7 lichen species from the phylum Ascomycota were identified, with foliose thalli and crustose thalli growing on living tree trunks, dead bark, and rocks. The presence of crustose lichens indicates relatively good air quality in the region. The diversity of fungi and lichens in the Waitatiri watershed highlights its importance as a local biodiversity habitat. Their ecological roles as decomposers and environmental bioindicators emphasize the need for watershed ecosystem conservation to ensure environmental sustainability. Further research is required to explore the ecological and economic potential of the identified species and support conservation efforts.